Photodynamic therapy for solid tumors: A review of the literature. Issue 5 (18th June 2019) - Yanovsky, Rebecca L.; Bartenstein, Diana W.; Rogers, Gary S.; Isakoff, Steven J.; Chen, Steven T.
Abstract: Photodynamic therapy (PDT) utilizes a sensitizer agent and light to produce selective cell death. Dermatologists are familiar with PDT for the treatment of actinic keratoses and early nonmelanoma skin cancers, and recent studies have elucidated that PDT has resulted in improved morbidity and secondary outcomes for the treatment of various cancerous and precancerous solid tumors. Light source and dosimetry may be modified to selectively target tissue, and novel techniques such as fractionation, metronomic pulsation, continuous light delivery, and chemophototherapy are under investigation for further optimization of therapy. This article aims to review the expanding indications for PDT and demonstrate the potential of this modality to decrease morbidity and increase quality of life for patients. To illustrate these new indications, we provide a focused review of the latest literature on PDT for dermatologic and other solid tumors including gastrointestinal, peritoneal, lung, genitourinary, brain, breast, and head and neck. Data on efficacy, survival, and side effects vary across tumor types but support PDT for the treatment of numerous solid tumors. With new advances in PDT, indications for this therapeutic modality may expand.